Literature Review: Smart City and Smart Governance in Analysis (Universitas Medan Area, 2020)
This study aims to determine the development of research in the big theme of Smart City and Smart Governance in the last nine years. To find out about this, 100 relevant journals about its implementation in government with the previous 9 years issue from 2011 to 2019. This study used a qualitative research method with a literature review or a prior research process. The data used were selected from 9-year journal issues from 2011 to 2019. The journals used were the highest citation-published journals, the journals used were journals relevant to government activities, the application of smart city concepts in local government, and the application of service processes. To the community. The results of this study were obtained by the process of data analysis using the Nvivo 12 application. These results address the use of Technology, Information, and Communication (ICT) as the most dominant factor in the implementation of smart cities in the analysis of previous research. Research Will explain the development of research annually and per continent on the significant themes of Smart City and Smart Governance.